Síntese de nanopartículas de prata com uso do extrato de Gymneia platanifolia e efeito antibacteriano contra Escherichia coli e Staphylococcus aureus - Jesus, Vinícius Silva Bastos de (2025)
Antimicrobial resistance (AMR) has emerged as a serious global public health problem caused by the misuse of drugs, which has resulted in increased morbidity, with frightening expectations if there are no effective measures to control this disorder. In contrast to this disorder, silver nanoparticles (AgNps) are capable of acting as antimicrobials against fungi and bacteria, carrying active principles or acting alone against these microorganisms. These AgNps can be synthesized in several ways, including using biological compounds such as microorganisms and plants, aiming for a more environmentally friendly process. The objective of this work was to synthesize AgNps with extract of the plant Gymneia platanifolia (Mart. ex Benth.) Harley & J.F.B. Pastore, so that they could be tested in vitro for bacterial inhibition. The formation of nanoparticles was verified by Ultraviolet–Visible Molecular Absorption Spectroscopy with absorption peak at 410nm and high-resolution transmission electron microscopy (HR-TEM) indicating face-centred cubic structure. These were characterized by HR-TEM with an interplanar distance of 0.236 nm in the <-1-2-1> direction; 79.88 nm of hydrodynamic length and -46.92 mV of Zeta Potential. Inhibitory capacity of AgNps against Escherichia coli and Staphylococcus aureus was identified. Therefore, the use of AgNps is promising for drug development in the coming years.